Perspectives on Teachers' Work in One Ontario Remote First Nation Community - Burleigh, Dawn V (Scholarship@Western, 2016)
The nature of teachers’ work in one northern Ontario remote First Nation community is explored through three articles that address the following questions: Why do teachers work in the North? What contributes to teacher retention and attrition? And, how do teachers navigate the professional and personal boundaries of their lives as teachers in the North? The articles are based on a case study of teachers’ work in one community and use data collected through interviews with 15 teachers, focus groups with sub-sets of those teachers, and observations collected as field notes. Article 1, Teacher attrition in a Northern Ontario remote First Nation community: A narrative re-storying, explores the shared experiences of teachers as they discuss the professional and personal factors that contribute to their retention and attrition. Article 2, Teaching and fear: Teachers’ work in a Northern Ontario remote First Nation community, unpacks how the emotion of fear mediates teachers’ experiences within a colonizing system. Article 3, Understanding roles and relationships: Teachers’ work in a Northern Ontario remote First Nation community, explains how teachers negotiate their roles and relationships with students, other teachers, families, and the community and uses the heuristic categories of pedestal people, transitioners, relationship builders and community integrators to explore the range of approaches teachers employ. Although the focus of each article is distinct, the general nature of teachers’ work was found to be deeply marked by complexity because of the relational conditions of their work. To be understood, the work of teachers must be positioned within discourses of power, colonization, the ongoing legacy of residential schools, and current decolonizing efforts. Practice-based policy suggestions such as mentorship and orientation programming, professional learning circles, and community-based activities are made to address challenges identified by the research. In addition, calls for equitable funding, continuing or ...